(3GdeTcdGJ GdYedjI aj OYGhi GdWdGb hGdaSN hGdNdY ddeUQjjf GdeSdejf hZjQ GdeSdejf (B/s - (3GdHfG, ceGd UGdMs ((3GdbGgQI (B:s (3YGde GdcJH,s, 2001)
(3jJWQb Edi bVjI GdWdGb hGdaSN hGdNdY aj GdTQjYI hGdbGfhf hGdbVGA heHGOF GdfbV hGdeMGce GdTQYjI(B.s
(3jTJed Ydi GQLGYGJ HHddjhLQGajIs
Keywords: (3GdWdGbs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdRhGLs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdCMhGd GdTNUjI dZjQ GdeSdejfs